Research Support In Policy Formulation At The Border Management Agency Of North Central Timor District - Yohanes Fritantus; Makarius Erwin Bria (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
This study aimed (1) to analyze the role of research results in the formulation of border management policies in North Central Timor Regency conducted by the Regional Border Management Agency of North Central Timor Regency and (2) to analyze the obstacles faced by the Regional Border Management Agency in applying research results in the process of the policy formulation. The applied research approach was the descriptive qualitative method. This method was used to obtain data regarding the role of research results in the formulation of border management policies in North Central Timor Regency and the constraints faced by the Regional Border Management Agency in applying research results in the process of the policy formulation. Furthermore, data were collected using an in-depth interview, observation, and documentation.The results showed that the role of research results began to get attention at the stage of problem formulation in the Regional Border Management Agency of North Central Timor Regency to identify strategic issues related to border management in North Central Timor Regency. However, the use of research results in the formulation of policies has not been maximized. It was because of as follows. (a) Although published research results are easy to access, some researchers whose research is approved by the Regional Border Management Agency of North Central Timor Regency do not submit their research reports; (b) Research that is communicated effectively in the form of advocacy is conveyed by researchers through dissemination and intensive discussions as policy recommendations; (c) The time variable is the main factor for the effectiveness of the use of research results in the formulation of border management policies by the Regional Border Management Agency of North Central Timor Regency.